Anthracofibrotic Lymph Node of Neck Mimicking Metastatic Malignant Melanoma in a Patient With Gastric Cancer. (October 2019) - Lee, Dong Hoon; Kim, Jo Heon; Cho, Sang Hee; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Extrathoracic anthracofibrosis in head and neck region is of extremely rare occurrence and can be confused with malignancy. In this article, we report an unusual case of an anthracofibrotic lymph node of neck that was mistaken for metastatic malignant melanoma in a gastric cancer patient. Because the incidence of an anthracofibrotic lymph node of the neck is very low, it is important to distinguish it from other diseases, including malignancy or metastasis, especially in patients with a cancer history. Thus, pathological diagnosis of anthracofibrosis is necessary to make an accurate diagnosis and find appropriate treatment.